Capacitor Motor as Low-Power, Low-Speed Single-Phase Generator - Hari Santoso; Rini Nur Hasanah; Budiono Mismail; I Nyoman Gde Wardana (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
In this paper, some results of experiment on modification of induction motor into generator are described. Not as usually done on three-phase motor, the modification has been done on capacitor motors normally supplied with single-phase source. The resulted induction generator should be able to self-excite and has been intended for low-power, low-speed applications. These applications are prospective for example in rural renewable energy generations and as motors for some special electric vehicles. Machine modification instead of total design-production or new machine acquisition is considered more appropriate for remote rural electrification. Distance and transportation difficulties, unavailability of nearby machine industry, lack of human resources with ‘high-tech savvy’, besides the low purchasing power of population in remote rural areas are some reasons behind the consideration. Experiment results indicated that voltage generation up to nominal value is not always easy to attain in a capacitor motor, even when functioning beyond its synchronous speed. An additional pre-charged capacitor should be used to initiate voltage generation. During start-up, load and the pre-charged capacitor had to be removed from generator to avoid capacitor discharge. Load could then be added gradually once generator approached its nominal output value. It was also shown that in order to generate power the generator must be rotating over its synchronous speed. The resulted frequency values did not vary linearly to the rotation speed and the obtained efficiency was still low.